Da'wah Management of the Friday Worship Program in Gowa Regency - Suhardi, Suhardi; Xu, Shanshan; Xavier, Murphy (Journal International Dakwah and Communication, 2024)
The success of a program in an agency or organization is inseparable from the good management function implemented in the agency or organization. Likewise, the implementation of Friday worship in Gowa district lasted for decades and felt many benefits by the community inseparable from the implementation of good da'wah management. This type of research is classified as qualitative using a da'wah science approach. The data sources of this research are the Chairman of the Indonesian Ulema Council of Gowa Regency, the Head of the Social Service of Gowa Regency, the Committee for Friday Worship activities of Gowa Regency, the Coordinator of Friday Worship activities of Gowa Regency, the Dai of Friday Worship activities of Gowa Regency, the Head of Pallangga Sub-District, the Head of Villages and Villages in Pallangga Sub-District, Village Imams and Mad'u of Friday Worship activities of Gowa Regency consisting of civil servants, members of the Taklim Assembly, entrepreneurs, day laborers and the people of Gowa in general. Furthermore, the data collection methods used are observation, interview, and documentation. The results of this study show that: 1) The process of Jum'at Ibadah activities begins with planning, namely planning da'wah material, da'wah fields, preachers, and mad'u. The implementation of Friday Worship activities in Gowa Regency begins with the recitation of the holy verses of the Qur'an chanted by the Imam of the Great Mosque of Sheikh Yusuf Gowa Regency, and continues with remarks by the government, then this activity is continued with da'wah or lectures then closed with dhikr and prayer. Evaluation of Friday Worship activities is to discuss the problem of da'wah material, da'wah fields, preachers and mad'u. Friday worship activities in Gowa district by implementing good, structured and professional da'wah management, and directly supervised by the Gowa district government in this case the Regent.